2011
DOI: 10.1248/cpb.59.1250
|View full text |Cite
|
Sign up to set email alerts
|

Spirocyclic Acylphloroglucinol Derivatives from <i>Hypericum beanii</i>

Abstract: Polyprenylated acylphloroglucinols, featured a highly oxygenated bicyclo[3.3.1]-nonane-2,4,9-trione or bicyclo[3.2.1]-octane-2,4,8-trione core decorated with C 5 H 9 or C 10 H 17 (prenyl, geranyl, etc.) side chains, were only isolated from the Guttiferae plants so far.1) This type of metabolites were reported to possess a wide variety of biological activities such as antimicrobial, antidepressant, antioxidant, cytotoxic, and anti-human immunodeficiency virus (HIV) effects. 2-7)As an important member of the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Apart from ten degrees of unsaturation occupied by three double bonds, three carbonyls, and a phenyl group, the remaining ones required a tricyclic ring system for 1. The above information suggested that 1 was a PSAP, whose NMR spectra were similar to those of hyperbeanol A (Chen et al, 2011). The 1 H-1 H COSY spectrum indicated four proton spin systems represented as bold lines (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Apart from ten degrees of unsaturation occupied by three double bonds, three carbonyls, and a phenyl group, the remaining ones required a tricyclic ring system for 1. The above information suggested that 1 was a PSAP, whose NMR spectra were similar to those of hyperbeanol A (Chen et al, 2011). The 1 H-1 H COSY spectrum indicated four proton spin systems represented as bold lines (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…For structural elucidation of tomoeones D and B (Hashida et al, 2008), these researchers explained that the dramatically downfield shifted signal of C-13 in tomoeone D (d C 85.5) was ascribed to a change in relative configuration of C-13 from its epimer tomoeone B (d C 72.7, D = 12.8 ppm). However, in the case of hyperbeanols A and B (C-13 epimers) (Chen et al, 2011), the difference in chemical shift of C-13 between hyperbeanols A (d C 72.3) and B (d C 68.6) was not so obvious (D = 3.7 ppm), and the structure of hyperbeanol A was unambiguously confirmed by a single crystal X-ray diffraction analysis. In another case of the PSAPs, namely harrisotones B and C, two C-13 epimers, only a small difference (D = 3.5 ppm) was observed between the chemical shift of C-13 in harrisotones B (d C 73.0) and C (d C 69.5) (Yin et al, 2009).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations